PEMANFAATAN AGROFORESTRI TANAMAN RUMPUT GAJAH SEBAGAI PAKAN TERNAK DI DUSUN SREMBEN, WILAYAH RESORT WONOLELO, TAMAN NASIONAL GUNUNG MERBABU - Bebi Sylvia Muryanto; Danastri Nur Athaya Radya Putri (Yayasan Nusantara Hasana Berdikari, 2023)
Elephant grass (Pennisetum purpureum) is a grass plant commonly used by the community as animal feed such as cows, buffaloes, and goats. The utilization of this crop can be done in an agroforestry system where the plant (Pennisetum purpureum) is planted in the same land management as wood plants as is done in the utilization zone of Mount Merbabu National Park. The use of Elephant Grass plants (Pennisetum purpureum) in this system needs to be considered because it is carried out close to protected areas. Land area management affects crop yields and their interactions as a sustainability of the agroforestry system carried out. The results showed that the people of Sremben Hamlet have implemented an agroforestry system in their field crops in the form of agricultural commodities and animal feed. The purpose of this study was to determine the agroforestry system applied in the use of Elephant Grass (Pennisetum purpureum) and its benefits for the economy by the people of Sremben Hamlet, Wulunggunung Village.